Health Promotion among Fish Sellers in Kedonganan, Bali - Putu Nita Cahyawati; Pande Ayu Naya Kasih Permatananda; I Gde Suranaya Pandit (Postgraduated Community Service Journal, 2025)
Bali is internationally known as a top tourist destination. In this community service program, the target group consisted of fish vendors affiliated with the KUD Mina Segara. The main goal was to provide education and mentoring, focusing on environmental cleanliness and promoting clean and healthy living behaviors in the workplace. The methods used included direct counseling and continuous assistance. Program success was measured by two key indicators: the implementation of one educational session and improvement in posttest scores compared to pretest results.A total of 17 partners participated in the program, most of whom reside in Kedonganan, with a few from Tuban, Renon, and Imam Bonjol. The participants were predominantly male (58.82%), with the majority aged between 51–60 years (41.18%). Most had low educational backgrounds, with 48.83% having completed only primary school, and some never attending formal education. The pretest results showed an average score of 18.82, which increased to 40 after the intervention. Although the posttest scores were not yet optimal, every participant showed improvement. These results indicate that the educational activity effectively increased their knowledge. The program was assessed as ‘Good’ for meeting all its intended indicators. Moving forward, continuous education and monitoring are considered necessary to reinforce and sustain the adoption of clean and healthy living practices among the fish vendor community in their working environment.